2019
DOI: 10.1039/c9fo01118h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial transglutaminase cross-linking on the quality characteristics and potential allergenicity of tofu

Abstract: This paper investigated the effect of MTGase cross-linking on the structure of soymilk protein and the improvement of physicochemical properties, digestibility and potential allergenicity of traditional tofu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…We believe that MTGase with inherent cross-linking ability has a higher propensity to them in spontaneously creating nanoower-like structure much more easily as compared to other enzymes or proteins. 43,45 This led us to explore the process for developing bio-catalytically active microbial transglutaminase nanoowers. MTGase serves as a glue that binds the petals together in the nanoower.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that MTGase with inherent cross-linking ability has a higher propensity to them in spontaneously creating nanoower-like structure much more easily as compared to other enzymes or proteins. 43,45 This led us to explore the process for developing bio-catalytically active microbial transglutaminase nanoowers. MTGase serves as a glue that binds the petals together in the nanoower.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the structure of soybean protein can be altered during processing. The molecular conformation of soybean proteins (β-conglycinin and glycinin) occurs via natural protein denaturation, aggregation, and subunit dissociationassociation (Chen & Ono, 2014;Zhu et al, 2019). Recently, enzymatic processing is employed to enhance the quality parameters of soybean products and to further reduce their immunoreactivity and allergenicity.…”
Section: Soybean Allergymentioning
confidence: 99%
“…Moreover, the levels of Th2-related cytokines were downregulated and the IFN-γ levels were increased, as measured by flow cytometry. Likewise, Zhu et al (2019) investigated the impact of microbial TG on the physicochemical properties and immunoreactivity of soymilk protein. Structural analysis indicated that TG treatment significantly altered the conformational structure of soymilk protein.…”
Section: Soybean Allergymentioning
confidence: 99%
“…The effects of MTGase alone or combined with conventional coagulants (saline and GDL) on the physical and chemical properties of tofu and the immunoreactivity were analyzed using SDS‐PAGE, circular dichroism spectrum, ultraviolet absorption spectrum, fluorescence spectrum, and other techniques (Zhu, Deng, et al., 2019). The results indicated that the higher‐order structure of soymilk protein was significantly altered by adding MTGase.…”
Section: Processing Conditionsmentioning
confidence: 99%
“…Freshly prepared by dissolving in cold water; then added to heated and cooled soymilk Mechanism: One molecule of TMC contains three magnesium ions and two citrate ions, and citrate should contribute to the pH drop needed to form a good gel network in tofu Mixtures of soymilk and enzyme in sealed cylinders (20 × 25 mm) with incubation at 37 • C for different times Mechanism: MTGase can assemble proteins with the help of isopeptide bonds Type of tofu: Soft or packed tofu Reference:Tang et al, 2007 Mixed coagulants Name: CS plus MC; CS plus MS Use concentration: CS = 35 mM, CS (30 mM) plus MC (5 mM) = 35 mM, CS (30 mM) plus MS (5 mM) = 35 mM, CS (25 mM) plus MS (10 mM) = 35 mM Use procedure: Freshly prepared SPI emulsions were mixed with stock CS dispersion and MC or MS solution; the mixtures were heated to 80 • C and coagulated for 30 min in a water bath. Mechanism: The cooperation effects of calcium and magnesium ions and a low concentration of Mg 2+ helped to form compact protein aggregates and facilitated gel homogeneity and resistance to deformation Cross-linked with MTGase for 3 hr at 50 • C, and further coagulated with brine and GDL for 30 min at 85 • C and transferred to a plastic mold and pressed for 3 hr Mechanism: The good hydrophilicity, high catalytic activity, and strong thermal stability are based on the properties of the MTGase Type of tofu: Pressed soft tofu Reference:Zhu, Deng, et al, 2019 …”
mentioning
confidence: 99%